Transformational and Transactional Leadership Styles: A Conceptual Framework of Their Relationship with Organizational Performance - Jangsiriwattana, Thamarat (KASEM BUNDIT JOURNAL, 2020)
PURPOSES: This paper aimed to study and develop a conceptual framework of the relationship between transformational, transactional, and mixed leadership styles and organizational performance. METHODS: A documentary approach to the study and integration of concepts, theories and existing research from various databases. RESULTS: The integration of concepts and theories on the 3 leadership styles, on the one hard, and their influence on subjective and objective organizational performances on the other. Consequently, a conceptual model for research on the relationship between leadership styles and organizational performance is presented. CONCLUSIONS: Concepts and theories on leadership and organizational performance can be integrated for a conceptual model for research to demonstrate the relationship between leadership styles and organizational performance.